DEIXIS ANALYSIS IN JOB APPLICATION LETTERS AND ITS APPLICATION IN TEACHING WRITING - Zulia Chasanah (Pendidikan Bahasa dan Sastra Universitas Muhammadiyah Purworejo, 2022)
Abstract. This research is concerned with deixis used in sentences of the job application letters. Based on the problem statements, the aims of this study are to explain kinds of deixis in job application letters and to describe the application of deixis in job application letters in teaching writing. The data of this study were taken from the sentences containing deixis in job application letter. The instrument of the research is the researcher. This study uses descriptive qualitative design because the researcher describes deixis found in the job application letter. The result shows that there are 405 (79.88%) person deixis, 1 (0.20%) place deixis, 4 (0.79%) time deixis, 43 (8.48%) discourse deixis, and 54 (10.65%) social deixis. The result of the application can be used for teaching writing at senior high school.Keywords: Deixis, Job Application Letter, Teaching Writing